Psychosocial profile of women reporting with breast related symptoms and their association with time taken for presentation, a hospital based study - Sood, Neelam; Sood, Medhavi; Bansal, Swasti; Singh, Dweep Chand (International Journal Of Community Medicine And Public Health, 2020)
Background: The paper aims to study psycho-socio- demographic factors of women presenting with breast symptoms, find their correlations with (TTP). Methods: This cross sectional study was conducted in the Breast diagnostic clinic of a tertiary care hospital over a period of 2 months with the aim to approach all those women attending the breast diagnostic clinics and who had not started any treatment so far. The data collection was done using self-administered questionnaire and interview based questionnaire as required for a period of 2 months. 80 patients were included in the study. Their socio-demographic data, health seeking behaviour were collected and personality traits, life orientation and coping styles were assessed using the standardized tests. Descriptive, correlation analysis and stepwise linear regression followed by logistic regression, using SPSS20 software. Results: TTP was long with mean 6months. It was found to be negatively associated with size of the lump and education and positively with awareness about risk of cancer. Life orientation styles and personality traits showed no correlation. Pessimism was the seen in the majority of women. Conclusions: Education and increasing awareness about risk of cancer in the women can help them to report for treatment without delay. The understanding of coping skill, life orientation and personality domains and their relationship with TTP in the pre-diagnostic stage can help in future planning strategies during the course of treatment for breast cancer.